Mechanical Vibrations. Theory and Applications - Kelly S. G. Graham (Stamford, Cengage Learning, 2012)
Mechanical Vibrations.Vibrations is one of the first courses where students learn to apply the knowledge obtained from mathematics and basic engineering science courses to solve practical problems. While the knowledge about vibrations and vibrating systems is important, the problem-solving skills obtained while studying vibrations are just as important. The objectives of this book are twofold: to present the basic principles of engineering vibrations and to present them in a framework where the reader will advance his/her knowledge and skill in engineering problem solving.